S58 Pulmonary Langerhans' Cell Histiocytosis (PLCH): a New National Register. (16th November 2010) - Mason, R H; Foley, N M; Hetzel, M R; Branley, H; Suntharalingam, J
Abstract : Introduction and Objectives: PLCH is a rare interstitial lung disease, linked to cigarette smoking and, in some cases associated with respiratory failure and death. Limited UK data have been published and hence little knowledge exists of the diagnostic and treatment practices employed by UK Respiratory physicians. Our study aims to characterise the epidemiological, clinical, histological, radiological and prognostic indicators in a nation wide cohort of patients with PLCH. This study aims to follow the patient journey from point of diagnosis, regardless of the mode of diagnosis, looking at patient demographics and clinical outcomes in the UK population. Methods: UK Respiratory Consultants were contacted to request details for 71 patients with known PLCH, who had previously been registered on the BTS Orphan Lung Disease (BOLD) database. Patients were sent a consent form and questionnaire. Once written consent was obtained, consultants were sent a questionnaire requesting medical information. The patients' GPs have provided current medication and past medical history information. Results: Details on 55 patients were received (including 10 deceased and, 4 lost to follow-up). 17 patients (8 males), have returned a completed consent form and questionnaire so far, and were included for analysis. Age at presentation 32.0 years (SD13.7). Presenting symptoms : Shortness of breath 70.5%, pain 47.1%, pneumothorax 11.8%, cough 29.4% and 5.9% asymptomatic (diagnosed incidentally). Smoking status : Ex 88.2%, current 6.0% mean (SD) 22 (27.2) pack years, and 6.0% never smokers. 23.5% admitted limited exposure to cannabis. Diagnosis : 82% patients had had an HRCT scan and 64.7% an open lung biopsy. Diseasecourse : Symptoms resolved 35.3%, same 41.2% and 23.5% had slowly progressed. 47.0% pneumothorax, 53.0% have received treatment either chemotherapy 29.4% (Chlorambucil (2), 2-Chlorodeoxyadenosine (2), Azathioprine(1)) or, an operation for recurrent pneumothorax (23.5%) 1 patient is on the waiting list for a lung transplant. Patients' opinion of Doctors' knowledge of PLCH : High 35.3%, medium 23.5%, Med/low or low 41.1%. Conclusions: Although small, this early dataset indicates a high prevalence of smoking in our UK cohort and, that despite advances in CT a high percentage of patients are still diagnosed with an open lung biopsy.